ITEP Lectures on particle physics and field theory - Shifman, M. A. (World Scientific, 1999)
This two-volume book is a collection of some of the best of those lectures. The lectures written in the 1980's and early 1990's have been revised and updated specifically for this publication. The lectures in this book are intended for beginners - graduate students and young researchers - who are about to delve into the intricacies of the theory. The book will serve as a comprehensive reference and textbook for all graduate students and researchers interested in modern particle physics. It will also be a useful guide for lecturers.